Astronomia no ensino médio: uma proposta de curso com foco na aprendizagem significativa e uso de ambiente colaborativo como ferramenta de tecnologia digital. - Anastacio, Marco Antonio Sanches (2020)
Astronomy has long been part of people's fascination. In this context, as it is one of the oldest sciences and with a multidisciplinary character, Astronomy is a potentially relevant topic for competences and skills development in High School, as it involves a combination of science, technology, and culture, allowing students understanding and reflecting on issues such as where they came from, where they are and where they are going. However, although their topics are addressed in basic education under the theme “Universe, Earth and life”, mainly within the contents of the disciplines of Natural Sciences, their approach in High School ends up being relegated to the background, often due to poor quality teaching material and the teacher's lack of preparation to deal with the subject. The research objective was to present a proposal for an Astronomy course with a focus on meaningful learning and the use of a collaborative environment as a technological tool. The course proved to be a viable possibility of working on the topic in High School, taking advantage of the recent introduction by the National Curriculum Common Base of training scripts, which allow the exploration and deepening of knowledge of interest to students. The use of the virtual environment allowed a hybrid teaching experience to be taken to High School, which promoted student involvement. At the end, the statistical analysis of the pre and post-test indirectly evidenced the occurrence of significant learning in the 33 students who participated in the course.